Tasks and means of therapeutic exercises in patients with breast cancer in pre- and postoperative periods - T. I. Grushina (Опухоли женской репродуктивной системы)
The mainstay of radical treatment for patients with breast cancer (BC) is a surgical intervention: radical mastectomy (RME) of different modifications or organ-sparing operations. In the preoperative period, the tasks of therapeutic exercises (TEs) are psychological preparation of a patient for active participation in his / her treatment, as well as complete breath training. Classes are done in a group of convalescents, by applying dynamic and static breathing exercises. In the early postoperative period, the tasks of TEs are to prevent hypostatic pneumonia, surgical-site shoulder joint stiffness and to improve systemic and regional blood and lymph circulation. Analysis of 1235 patients who had undergone RME and 212 patients who had radical resection showed that restricted shoulder joint motion due to hand immobilization in an adducted position and late initiation of TEs occurred in 44.6 and 33.5 % of the patients, respectively. Individual TEs classes include breathing exercises, position treatment, and special exercises to restore shoulder joint function and to control posture. Lymphadenectomy and failure to ligate intersected lymphatic vessels lead to inevitable lymphorrhea and seroma. Analysis of 1447 patents indicated that early initiation of TEs failed to affect seroma duration and extent and wound dehiscence. In the latter (that, according to the author»s data, occurs in 3.7 % of cases after RME and in 9.2 % after preoperative radiotherapy), TEs are limited by position treatment until the wound heals or secondary sutures are applied. The tasks of the late postoperative period are recovery of the full range of shoulder joint motion, normal posture, cardiovascular and respiratory adjustments to increased physical exercises, and general tonic exposure. The paper gives TEs sets developed for each period.